Quality of life of stroke survivors and their family caregivers at selected referral rehabilitation care centers - Khaw, Wan-Fei (2017)
Stroke disability results in hardship to both patients and families. Care for stroke patients can be stressful and lead to deterioration of quality of life (QOL). Despite the large number of stroke cases, limited local data are available on the impact of stroke on QOL of stroke survivors and caregivers, and little is known regarding the interdependence of QOL within the dyad. Thus, this study was developed to evaluate overall QOL of stroke survivors and caregivers, and determined factors predicting QOL. Dyadic analysis using Actor-Partner Interdependence Model (APIM) examined whether stroke survivor’s and caregiver’s QOL at baseline, predicts his or her own QOL at six months follow-up (actor effect) and partner’s QOL at follow-up (partner effect). This was a prospective study that involved 160 stroke survivors and 160 caregivers recruited from neurology clinics in Hospital Kuala Lumpur and Hospital Rehabilitasi Cheras in Klang Valley, Malaysia. The six months follow-up included 38 stroke survivors and 38 caregivers. Socio-demographic and medical conditions, caregiving appraisal, coping strategies and QOL were obtained from stroke survivors and caregivers. The data were entered and analysed using the IBM SPSS for Windows, Version 22.0 and IBM SPSS AMOS, Version 22.0. Univariate analysis was used to clean and check the quality of data. Bivariate analysis was performed to examine the bivariate relationships among predictor variables and stroke survivor’s and caregiver’s QOL. Confirmatory factor analysis (CFA) was used to test dimensionality of the QOL measure of five indicators: physical health, mental health, general health, peace, and faith. Path analysis was used to determine the direct and indirect effects of predictors on QOL in both stroke survivors and caregivers, and to assess the APIM model for survivor-caregiver dyads. CFA results indicated acceptable goodness-of-fit of one-factor QOL model (χ2(12) = 42.265, p < 0.001; RMSEA = 0.063; SRMR = 0.038; CFI = 0.970), which included five indicators: physical health, mental health, general health, peace, and faith. Stroke survivors rated lower QOL scores compared to caregivers (M = 57.96, SD = 15.06 versus M = 45.50, SD = 16.65). Six determinants with both a direct and indirect effect on the QOL of stroke survivors were age, duration of stroke, stroke severity, cognitive function, physical function, and psychological distress. Seven determinants with both a direct and indirect effect on the QOL of stroke caregivers were caregiver’s age, stroke severity, social support, adaptive coping, maladaptive coping, caregiving burden, and caregiving satisfaction. Actor effects between stroke survivor’s QOL (β = 0.79, p < 0.001) and caregiver’s QOL (β = 0.76, p < 0.001) at baseline and follow-up were significant. This indicates that stroke survivor’s and caregiver’s QOL at baseline were positively related to their own QOL at 6-months-follow-up. These findings highlight the overall QOL score integrates all the measures of health status of stroke survivors and their caregivers. The APIM dyadic analysis provides insight into the relationships between stroke survivor’s and caregiver’s QOL. Thus, this study definitively indicates the necessity for arranging interventions targeting both stroke survivors and family caregivers, to enhance their QOL in the rehabilitation process.